2013
DOI: 10.1186/1471-2164-14-429
|View full text |Cite
|
Sign up to set email alerts
|

The duration of gastrin treatment affects global gene expression and molecular responses involved in ER stress and anti-apoptosis

Abstract: BackgroundHow cells decipher the duration of an external signal into different transcriptional outcomes is poorly understood. The hormone gastrin can promote a variety of cellular responses including proliferation, differentiation, migration and anti-apoptosis. While gastrin in normal concentrations has important physiological functions in the gastrointestine, prolonged high levels of gastrin (hypergastrinemia) is related to pathophysiological processes.ResultsWe have used genome-wide microarray time series an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 72 publications
(109 reference statements)
2
20
0
Order By: Relevance
“…This indicates that gastrin-induced SIK1 expression might be under negative control of a gastrin-induced repressor. Results from our genome-wide time series experiments in AR42J cells revealed that SIK1 is a primary gastrin-induced gene [4]. Treating AR42J cells with cycloheximide (CHX) (to block de novo protein synthesis) did not inhibit Sik1 mRNA induction by gastrin (Figure S1B and [4]), suggesting that SIK1 is a direct target gene of gastrin signalling.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…This indicates that gastrin-induced SIK1 expression might be under negative control of a gastrin-induced repressor. Results from our genome-wide time series experiments in AR42J cells revealed that SIK1 is a primary gastrin-induced gene [4]. Treating AR42J cells with cycloheximide (CHX) (to block de novo protein synthesis) did not inhibit Sik1 mRNA induction by gastrin (Figure S1B and [4]), suggesting that SIK1 is a direct target gene of gastrin signalling.…”
Section: Resultsmentioning
confidence: 95%
“…Results from our genome-wide time series experiments in AR42J cells revealed that SIK1 is a primary gastrin-induced gene [4]. Treating AR42J cells with cycloheximide (CHX) (to block de novo protein synthesis) did not inhibit Sik1 mRNA induction by gastrin (Figure S1B and [4]), suggesting that SIK1 is a direct target gene of gastrin signalling. Gastrin induced higher levels of SIK1 in presence of CHX, supporting the assumption that SIK1 expression might be under negative control of a gastrin-induced repressor.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In recent years, however, several lines of evidence have emerged to suggest that there is much more to the biology of gastrin than is indicated by earlier work 25, 35. Gastrin has been shown to display proliferative,36, 37 antiapoptotic,38 and cell migration39 properties. In previous reports, the concentration of gastrin in serum was found to be significantly increased during myocardial infarction 13.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT pathway has been shown to play a role in the antiapoptotic effects of gastrin 49. Sustained gastrin stimulation enhances cell survival, in part by decreasing apoptosis via the ERK1/2 pathway 38. In addition, activation of JAK2 (janus kinase 2)/STAT3 pathway by glycine‐extended gastrin has been shown to increase the survival of gastrointestinal tumor cells 50.…”
Section: Discussionmentioning
confidence: 99%